Os processos de permanência dos estudantes do PROEJA do IFSul, Campus Pelotas. - Katrein, Beatriz Helena Siqueira (2012)
This study had as main objective getting to know the factors that constitute the stories of permanence of students belonging to the PROEJA-IFSul-Pelotas Campus. The research, which is qualitative in terms of approach, has as investigative focus a group of eight students from the second class of PROEJA, who entered, remained in the course and graduated as Technicians in Informatics Maintenance and Support, in August 2011. The thesis, besides presenting different theoretical approaches that discuss the exclusion produced inside schools, also addresses the debate around the challenge of bringing together the Youth and Adult Education and the Vocational and Technological Education in the constitution of PROEJA. It presents a brief survey of the fields in dialogue in such educational context and a description of PROEJA as educational policy of widening the access of youth and adults to basic education that makes mid-level schooling and professionalization possible through an integral education of workers. In this research, it has been used as data collecting instruments semi-structured interviews and document analysis. The methodology adopted for data analysis has been content analysis, oriented by two complementary theoretical approaches: one referring to Charlot s study (1996), which identifies different articulations of mobilization processes attributed by suburban students to the meaning of going to school and keeping studying there, and the other, referring to studies that generate sociological characteristics from mixed pedagogical practice, proposed by Moraes and Neves (2009), grounded on Bernstein s Pedagogic Discourse Theory (1996). Following such procedure, it has been analyzed the permanence from the students mobilization toward the school (the meaning attributed to the fact of their going back to school); from the students mobilization at school (the investment in the study), and the references to sociological characteristics of the pedagogical practice used in PROEJA classes. The research has shown that the students remained at PROEJA mobilized by the meaning they attributed to the return to school (schooling; professionalization; life improvement), experiencing, in its interior, mobilization processes that have been identified by three themes, from which the most highlighted was the acquaintanceship and the support from colleagues and teachers. The study has also pointed the respect to the different timings of learning acquisition, the open communication between students and teachers, and the sharing of spaces and materials as the main characteristics of PROEJA pedagogical model that have facilitated students permanence in the course.